Demo: Sword Fight With Smartphones - Zhang, Zengbin; Qiu, Jian; Chu, David; Moscibroda, Thomas (9th ACM Conference on Embedded Networked Sensor Systems, 2011)
We present a demonstration of a phone-to-phone Sword Fight! game. It utilizes our solution for achieving high speed 3D continuous localization described in the accompanying conference paper. The approach uses acoustic cues based on time-difference of arrival and power level. It assumes at least two microphones and one speaker per phone, which is common on new smartphones. Accelerometers and digital compasses assist in resolving ambiguous acoustic-only localization. Continuous localization is achieved with the aid of a loose time synchronization protocol and a Kalman filter. Lastly, practical gameplay issues are addressed.